Social Distancing dalam Saf Salat Berjamaah; Perbandingan Ulama dalam Mazhab - Nasir, Agus (Mazahibuna: Jurnal Perbandingan Mazhab, 2020)
This article outlines the views of scholars about the rules of safari in congregation while maintaining distance. The approach used is normative by trying to expose normative arguments from the view of ulama. The results show that in relation to the social distancing safty law in congregational prayers, the prayers remain valid and are allowed to do as an effort to break the chain of the spread of the corona virus. And part of our endeavors to Allah Almighty. and of course worship continues to be increased, prayer never interrupts, and our conviction persists that God will immediately raise this plague. Keywords: Social Distancing; Congregational Prayers.